THE EFFECT OF THINK PAIR AND SHARE METHOD ON STUDENT SPEAKING SKILL IN SMAN BANDARKEDUNGMULYO - IKA ZULAICHAIKA (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2018)
ABSTRACT This study aims to describe the results of students learning English by using speaking skills by applying the method of pair think and share on congratulation and complimenting material in class X SMAN Bandarkedungmulyo. This study uses paired design by measuring students' speaking skills in congratulation and complimenting material. The analysis results show that with the pair think and share method applied students are more interested in speaking English. Student responses to the pair think and share (PTS) learning method are positive. KEYWORDS: pair think and share, speaking skill, congratulation ABSTRAK Penelitian ini bertujuan untuk mendeskripsikan hasil belajar bahasa Inggris siswa dengan menggunakan keterampilan berbicara dengan menerapkan metode pair think and share pada materi ucapan selamat dan pujian di kelas X SMAN Bandarkedungmulyo. Penelitian ini menggunakan desain berpasangan dengan mengukur kemampuan berbicara siswa pada materi ucapan selamat dan pujian. Hasil analisis menunjukkan bahwa dengan metode pair think and share yang diterapkan siswa lebih tertarik untuk berbicara bahasa Inggris. Respon siswa terhadap metode pembelajaran pair think and share (PTS) positif. KATA KUNCI: pair think and share, keterampilan berbicara, selamat